More than one intracellular processing bottleneck delays the secretion of coagulation factor VII - Bolt, Gert; Kristensen, Claus; Steenstrup, Thomas D. (Thrombosis and Haemostasis, 2008)
Coagulation factorVII (FVII) is a vitamin K-dependent glycoprotein that undergoes extensive post-translational modification prior to secretion. Secretion of FVII proteins from producer cells is a slow process. To identify bottlenecks for the transport of FVII through the secretory pathway of FVII-producing cells, we analysed the processing of intracellular FVII by pulse-chase of FVII producing CHO cells followed by radioimmuno precipitation, SDS-PAGE, and autoradiography. FVII was coprecipitated with GRP78 and vice versa for at least three hours after synthesis of the labelled FVII, suggesting that nascent FVII is retained in the endoplasmic reticulum (ER). Judged from barium citrate precipitation assay, gamma-carboxylation of the pulse-labelled FVII was a slow process requiring several hours and seemed to be the most important bottleneck in the intracellular processing of FVII. Nevertheless, FVII was not released from the cells immediately after gamma-carboxylation. Gamma-carboxylated FVII accumulated in the cells and migrated as a band with reduced mobility compared to uncarboxylated FVII. This shift in migration was caused by N-glycan processing in the Golgi complex. Thus, the release of FVII from producer cells is delayed by at least two bottlenecks. The major bottleneck appears to be gamma-carboxylation, which determines the rate of transport of FVII out of the ER. Another bottleneck retains FVII in the cells after processing of the N-glycans into complex chains. Cells with an intact gamma-carboxylation machinery appear to posses mechanisms that protect nascent FVII from intracellular degradation and keep FVII in the ER until it is gamma-carboxylated.
Keywords: Factor VII; protein processing; post-translational; gammaarboxylation; glycosylation